The legal framework for incorporation of islamic venture capital in Nigeria : the Malaysian model - Mikail, Sa'id Adekunle (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2013)
The ultimate objectives of this study are twofold. The first is to examine possible incorporation of Islamic venture capital in Nigeria. The second is to examine whether the Malaysian regulatory model would be appropriate in the Nigerian milieu. Since Islamic venture capital is a new phenomenon, this study provides an overview of conventional venture capital as a precursor of the Islamic model. Furthermore, this study provides some introductory remarks on the development of Islamic venture capital while focusing on recent trends and regulatory policies. This includes pre-Islamic partnership modes, early Islamic partnership modes, modern evolution and application of venture capital, and contemporary application of Islamic venture capital. With special emphasis on Islamic venture capital, the study examines Shari'ah modes of investment, Shari'ah compliance requirements and legal requirements for incorporating Islamic venture capital followed by allied matters. The methodology used in this study involves both doctrinal and non-doctrinal methods. It employs qualitative method using phenomenological research based on purposefully selected samples for interviews on the Malaysian regulatory framework for Islamic venture capital with a view to assessing its appropriateness for Nigeria. In the Nigerian context, the descriptive approach of doctrinal research is applied. The research findings reveal that the Malaysian model is appropriate for Nigeria. Nevertheless, the study also finds that the major constraints of Islamic venture capital in Nigeria are political will, regulatory requirements and poor infrastructures. However, there are some essential issues to be addressed in addition to legal and regulatory amendments for incorporating Islamic venture capital in particular and Islamic financial system in general. First, there must be political will to incorporate the principles of Islamic finance into the Nigerian financial system. Second, the right technical infrastructure for a sound and robust socio-economic environment that is conducive for venture capital, whether Islamic or conventional, is of paramount importance.